Potentials and projections of freshwater resources in Sub-Saharan Africa; focus on Nigeria (2009)
This paper discusses the abundance of freshwater availability in Nigeria which is approximately 0.51 % of world freshwater resources. It further highlights the projected freshwater crises in Nigeria and Africa as a whole. Based on analyzed country data retrieved from International Organizations.Nigeria and in fact many developing countries in Sub Saharan Africa is presently termed water secure based on total Actual Renewable Water Resources, but projections into the nearest future (2025) classify Nigeria as water stress/scarce due to lack of economic, financial and skilled human resources to tap water for basic human needs, food production and maintenance of freshwater ecosystem. Causes of this projected impending danger were attributed to increase in freshwater quantity supply made available through unsustainable water resources development and inappropriate water management programmes.